An Analysis of Phrase Structures in the First Movement of Leo Brouwer’s Elogio De La Danza (1964) - Focsaneanu, Bogdan Vasile (Université d'Ottawa / University of Ottawa, 2012)
This study examines phrase and larger formal structures in the first movement of Leo Brouwer’s Elegio de la Danza (1964), a work that draws on tonal and post-tonal traditions. By adapting key features of the tonal motive, as described by Douglass Green, and the tonal period, as proposed by Green and William Caplin, the model seeks to provide a tool for the discussion of phrases and larger forms in Brouwer’s work. An analysis of primary parameters, such as melody, harmony, and rhythm, provides the means to discuss how the composer articulates beginnings and endings of statements and responses, which are then grouped into antecedent and consequent phrases. These periods articulate large-scale sections, which outline a ternary formal design. Secondary parameters (dynamics, tempo markings, instrumental markings) further contribute to the identification of formal structures in Brouwer’s work.
Keywords: Leo Brouwer; Elegio de la Danza; motives; phrase structure; formal analysis; period; guitar; post-tonal; Douglass Green; Christopher Hasty; William Caplin